Biomechanical comparison of different framework materials in mandibular overdenture prosthesis supported with implants of different sizes: a finite element analysis - Elifnur Güzelce S (BMC, 2023)
Abstract Background The aim of this study is to evaluate the stresses on the supporting bone, implants, and framework materials under masticatory forces in mandibular overdenture prostheses modeled with different framework materials and different implant types, using the Finite Element Analysis (FEA). Methods For the finite element modeling, two identical mandibular jaw models were created; one with two standard (diameter:4.1 mm/12 mm length) and the other with two mini-implants (diameter:2.4 mm/12 mm length) were placed in the canine teeth area. The polymethylmethacrylate (PMMA) denture was modeled upon them, supported by Cobalt Chromium alloy (CoCr), Poly-ether ether ketone (PEEK), and Zantex materials with framework. No framework was added as a control model; only PMMA overdenture prosthesis was modeled. Results Regardless of the framework materials of the overdenture prostheses, the stress values ​​on mini-implants in all models yielded approximately two times higher results comparing to standard implants. More stress transmission was observed in the supporting bone and implants in the control prostheses and overdenture prostheses supported with respectively PEEK, Zantex, CoCr alloy frameworks, respectively. In the framework materials, more stress occurred on CoCr, Zantex and PEEK in that order. Conclusion In the light of this study, the use of mini-implants as an alternative to standard implants is not promising in terms of distribution and transmission of chewing stresses. As a framework material, standard rigid metal alloys were found to be more advantageous than polymer materials in terms of stress distribution.